Creation of GMP-Compliant iPSCs From Banked Umbilical Cord Blood - Tian, Pei; Elefanty, Andrew; Stanley, Edouard G.; Durnall, Jennifer C.; Thompson, Lachlan H.; Elwood, Ngaire J. (Frontiers in Cell and Developmental Biology, 2022)
Many clinical trials are in progress using cells derived from induced pluripotent stem cells (iPSC) for immunotherapies and regenerative medicine. The success of these new therapies is underpinned by the quality of the cell population used to create the iPSC lines, along with the creation of iPSCs in a fully Good Manufacturing Practice (GMP)-compliant environment such that they can be used safely and effectively in the clinical setting. Umbilical cord blood (CB) from public cord blood banks is an excellent source of starting material for creation of iPSCs. All CB units are manufactured under GMP-conditions, have been screened for infectious diseases, with known family and medical history of the donor. Furthermore, the HLA tissue typing is known, thereby allowing identification of CB units with homozygous HLA haplotypes. CB cells are naïve with less exposure to environmental insults and iPSC can be generated with high efficiency. We describe a protocol that can be adopted by those seeking to create clinical-grade iPSC from banked CB. This protocol uses a small volume of thawed CB buffy to first undergo ex-vivo expansion towards erythroid progenitor cells, which are then used for reprogramming using the CytoTune™-iPS 2.0 Sendai Reprogramming Kit. Resultant iPSC lines are tested to confirm pluripotency, genomic integrity, and stability. Cells are maintained in a feeder-free, xeno-free environment, using fully defined, commercially available reagents. Adoption of this protocol, with heed given to tips provided, allows efficient and robust creation of clinical-grade iPSC cell lines from small volumes of cryopreserved CB.